Factors impacting vaccine hesitancy toward Coronavirus disease-19 (COVID-19) vaccination in Brooklyn, New York. Issue 11 (2nd November 2021) - Smith-Norowitz, Tamar A.; Silverberg, Jonathan I.; Norowitz, Esther M.; Kohlhoff, Stephan; Hammerschlag, Margaret R
Abstract: The Coronavirus disease-2019 (COVID-19) pandemic led to the development of several candidate vaccines. However, current research suggests that the potential of successful vaccines is tempered by vaccine skepticism or hesitancy. If vaccine efficacy is 80%, then the herd immunity required from vaccination is about 75-90%. The aim of the current study was to study factors impacting COVID-19 vaccine hesitancy in a representative sample of adults (age≥18 years) in a COVID-19 hotspot Abbreviations: COVID-19: coronavirus disease-19